Determination of S-Adenosylmethionine and S-Adenosylhomocysteine by LC-MS/MS and evaluation of their stability in mice tissues - Krijt, Jakub; Dutá, Alena; Kozich, Viktor (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2009)
S-Adenosylmethionine (SAM) serves as a methyl donor in biological transmethylation reactions. S-Adenosylhomocysteine (SAH) is the product as well as the inhibitor of transmethylations and the ratio SAM/SAH is regarded as the measure of methylating capacity ("methylation index"). We present a rapid and sensitive LC-MS/MS method for SAM and SAH determination in mice tissues. The method is based on chromatographic separation on a Hypercarb column (30 mm x 2.1 mm, 3 microm particle size) filled with porous graphitic carbon stationary phase. Sufficient retention of SAM and SAH on the chromatographic packing allows simple sample preparation protocol avoiding solid phase extraction step. No significant matrix effects were observed by analysing the tissue extracts on LC-MS/MS. The intra-assay precision was less than 9%, the inter-assay precision was less than 13% and the accuracy was in the range 98-105% for both compounds. Stability of both metabolites during sample preparation and storage of tissue samples was studied: the SAM/SAH ratio in liver samples dropped by 34% and 48% after incubation of the tissues at 4 degrees C for 5 min and at 25 degrees C for 2 min, respectively. Storage of liver tissues at -80 degrees C for 2 months resulted in decrease of SAM/SAH ratio by 40%. These results demonstrate that preanalytical steps are critical for obtaining valid data of SAM and SAH in tissues.
Keywords: ledviny; S-Adenosylmethionine; tandemová hmotnostní spektrometrie; Kidney; S-Adenosylhomocysteine; Tandem Mass Spectrometry; Chromatography, Liquid; myši; Mice; mužské pohlaví; zvířata; játra; Mice, Inbred C57BL; Liver; Animals; Male; S-adenosylhomocystein; chromatografie kapalinová; myši inbrední C57BL; S-adenosylmethionin